2022
DOI: 10.1029/2021gl096628
|View full text |Cite
|
Sign up to set email alerts
|

It’s the Heat and the Humidity: The Complementary Roles of Temperature and Specific Humidity to Recent Changes in the Energy Content of the Near‐Surface Atmosphere

Abstract: Global change is a change in the energy balance of the planet. It is usually communicated to the public as a change in near-surface (2 m) air temperature (T a ), but some 90% of the excess energy has entered the oceans (Church et al., 2011;von Schuckmann et al., 2020) and T a is only part of the energy balance of the near-surface atmosphere (Peterson et al., 2011). The total energy (E, J) of a representative kilogram of air is the sum of its enthalpy, latent heat, kinetic energy, and gravitational potential:wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
3
3
0
Order By: Relevance
“…The near‐surface increase in Ta was indeed much larger over the same period (0.76°C) and so too was the amount of heat channeled into the latent term, with Te rising by 1.49. These near‐surface heating rates are in close agreement with those recently reported by Song et al (2022) and Stoy et al (2022).…”
Section: Climate Change and Atmospheric Energy Accumulationsupporting
confidence: 92%
See 1 more Smart Citation
“…The near‐surface increase in Ta was indeed much larger over the same period (0.76°C) and so too was the amount of heat channeled into the latent term, with Te rising by 1.49. These near‐surface heating rates are in close agreement with those recently reported by Song et al (2022) and Stoy et al (2022).…”
Section: Climate Change and Atmospheric Energy Accumulationsupporting
confidence: 92%
“…Te is closely related to human heat stress (Box 1), and has a relationship with how hot it feels that is more linear than other commonly used metrics (Figure 4). In line with concerns raised in the literature (Stoy et al, 2022), Figure 3d therefore communicates that moist enthalpy is climbing fastest in a region already with the highest values worldwide and on the frontline against the threat from deadly humid heat. This critical, impacts‐relevant message is obscured entirely by the dry‐bulb temperature trend.…”
Section: Air Temperature Trends Can Obscure Climate Change “Hotspots”supporting
confidence: 87%
“…It is plausible that 𝑇𝑒 would already be used more widely in glacier-climate modelling had there not been a historical observational bias towards the mid-latitudes 41 , where the advantages in Ѱ simulation do emerge, but not nearly so clearly. In recognizing the importance of directly including latent heat to track melt energy in the tropics, our work therefore accords with the growing appreciation that air temperature alone can be a poor indicator of climate change impacts for these latitudes 23,45,46 . This also has implications for identifying and communicating likely hot-spots of cryospheric change, because those regions experiencing the highest trends in 𝑇𝑎 might not correspond to the areas of greatest increases in 𝑇𝑒.…”
Section: Discussionsupporting
confidence: 63%
“…The widespread increase in land aridity and decrease in soil moisture (Berg et al., 2016; Dai, 2013; Huang et al., 2016; Mankin et al., 2019; Sherwood & Fu, 2014) suggest that the latent heat component of MSE should decrease over time, a deduction supported by some observational studies (Lutsko, 2021; Yu et al., 2021). Other studies have reported that, instead of offsetting each other, the latent MSE component change actually reinforces the sensible component increase (Matthews et al., 2022; Peterson et al., 2011; Stoy et al., 2022), further amplifying the T w trend. A key obstacle to understanding the role of latent heat in T w change is that humidity trend calculation is extremely sensitive to the choice of humidity variable.…”
Section: Introductionmentioning
confidence: 99%